Pengaruh Budaya Belajar Mata Pelajaran Akidah Akhlak Terhadap Dinamika Relasi Siswa Santri dan Siswa Non Santri di Kelas XI MA Hidayatul Mubtadiin Jati Agung Lampung Selatan - Diah Nuraini; Yuli Habibatul Imamah; Sarpendi Sarpendi (Departement of Mathematics Education, 2024)
The point of this examination is to decide the impact of the way of life of learning moral conviction subjects on the elements of the connection among santri and non-santri understudies in class XI MIA Mama Hidayatul Mubtadiin Sidoharjo Jati Agung South Lampung. This examination utilizes quantitative exploration techniques. The number of inhabitants in this review was class XI Mama Hidayatul Mubtadiin, adding up to 70 understudies. The examining procedure utilized was purposive testing, the example in this review was taken from class XI MIA II, adding up to 20 understudies, 14 santri understudies and 6 non-santri understudies. Information assortment utilized was as surveys, perception and documentation techniques. The information was handled and dissected utilizing the cross classification information examination technique (crosstab). The consequences of the examination show that the social language of learning moral conviction subjects by and large emphatically affects the elements of connections between santri understudies and non-santri understudies at Mama Hidayatul Mubtadiin. It very well may be seen from the consequences of the T Test computation (Fractional) that the impact of the way of life of learning moral conviction subjects on the elements of understudy connections between understudies utilizing the t test shows that tcount (2.453) > ttable (2.100), and the impact of the way of life of learning moral conviction subjects affects the elements of connections between non-santri understudies utilizing the t test, it was gotten t count (2.246) > t table (2.100). Subsequently, it shows that the learning society of moral conviction subjects affects understudies' social elements.